Doação de órgãos: meu corpo, minha sociedade - Bendassolli, Pedro Fernando [UNESP] (Universidade Federal do Rio Grande do Sul (UFRGS), Pós-Graduação em Psicologia, 1998)
A doação de órgãos é um problema de relevância social e científica, pois envolve as formas como a vida é perpetuada através do corpo de outra pessoa, especificamente por meio de seus órgãos. Quais são os fatores de resistência e de facilitação à doação de órgãos? Este artigo propõe um fator de resistência e um de facilitação. O primeiro, o narcisismo pelo próprio corpo; o segundo, o desejo de perpetuar-se a si mesmo e a vida.

Organ donation is a problem of social and scientific relevance because it involves the ways through which life is perpetuated across another person s body, specifically by its organs. What are resistance and facilitation factors to organ donation? This article proposes one factor of resistance and one of facilitation. The first, the narcissism of the own body; the second, the desire of perpetuate oneself and life.
Organ donation: my body, my society
Keywords: Doação de órgãos; corpo; simbolização do corpo; medicina; narcisismo; Organ donation; body; simbolization of the body; medicine; narcissism